Learning and student’s achievement factors in j-QAF Khatam al-Quran model - Hamdi Ishak; Mohd Hanafi Mamat; Mohd Faizulamri Mohd Saad; Sabri Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper aims to explore students’achievement and their practice level of learning factor in the j-QAF Khatam alQuran Model involving 291 respondents of standard five students for 2016 session at four primary schools in Bandar Baru Bangi. Sample selection method was based on strata random sampling method according to Krejcie and Morgan’s sample size determination table. Survey responses were obtained through a set of questionnaires. Statistical data analysis was performed using IBM SPSS Statistics version 23.0 software involving descriptive and inferential analysis. This paper concludes that the achievement of students from the grading aspect was at excellent level but the complete recitation of the Quran was still at moderate level. The findings showed that there were no significant differences in achievement based on gender but there were significant differences in the type of schools. Learning factor practice showed that the mean value of teaching and environmental factors was moderately high while the practice of parents and attitude factors was moderately low. The findings also showed no significant differences in the practice of learning factors in terms of different gender. This paper clarifies an overview of the type of school showed that teachers, parents and attitude do not remarks any significant differences but environmental factor show significant differences.